Organic–Inorganic Hybrid Indium Halide Perovskites with Near‐Unity Photoluminescence Quantum Yield - Hengguang Wang; Yueqi Shen; Congcong Gao; Shengze Ban; Jinyang Bi; Jianyi Huang; Bo Wu; Weihua Ning (Advanced Materials Interfaces)
Abstract Organic–inorganic hybrid halide perovskites (OIHPs) have garnered significant attention in the field of optoelectronic applications due to their unique quantum confinement structures, tunable bandgaps. However, the intrinsic low photoluminescence quantum yield (PLQY) has limited their further applications in optoelectronic devices. Herein, the synthesis of a lead‐free, 0D hybrid organic–inorganic indium‐based halide crystal, (PMA)₄In1−xCl₇·0.5H₂O: xSb3⁺ are reported, which exhibits strong orange emission through controlled Sb3+ ion doping. A remarkably photoluminescence quantum yield (PLQY) of 95.2% is achieved by the optimal composition, (PMA)₄In98.92%Cl₇·0.5H₂O: 1.08% Sb3⁺. Ultrafast transient absorption spectroscopy is employed to further investigate the influence of Sb3⁺ dopants and the origin of the bright emission. The light‐emitting diode (LED) fabricated using this material demonstrates an impressive luminance of 72,252 cd m⁻2 and exhibits stable orange emission under various applied biases. This study highlights the significant potential of Sb3⁺ doping in tuning the broadband emission of metal halides and demonstrates the promising applications of these metal halide crystals in areas such as lighting, dermatological therapy, wound healing, and indoor plant growth.